Market information: Getting the right price - Sindikubwabo, Innocent (Technical Centre for Agricultural and Rural Cooperation, 2009)
By making market information available on the internet, radio and mobile phones, a network of village centres has helped to improve farmers' incomes in Côte d'Ivoire.